동적 에너지 시뮬레이션에 기반한 지열원 및 공기열원 냉난방 시스템의 탄소배출량 분석 - 강연주(Yeonju Kang); 채호병(Hobyung Chae); 배상무(Sangmu Bae); 김권예(Kwonye Kim); 남유진(Yujin Nam) (설비공학 논문집, 35(10), 2023)
본 연구에서는 지열원 및 공기열원 시스템의 성능 분석을 수행하고, 시뮬레이션 결괏값을 토대로 전 과정평가법을 통해 탄소배출량을 정량적으로 산정하였다. 그 결과는 다음과 같다. (1) 난방기간 GSHP 시스템의 평균 COP는 2.9, ASHP 시스템 COP는 2.4로 산출되어 GSHP 시스템이 약 17% 더 높게 나타났다. 냉방기간 GSHP 시스템의 평균 COP는 3.8, ASHP 시스템 COP는 2.7로 산출되어 GSHP 시스템이 약 28% 더 높게 나타났다. (2) 1년 운영 시 탄소배출량은 GSHP 시스템 7,915 kgCO2-eq, ASHP 시스템 6,822 kgCO2-eq으로 ASHP 시스템이 14% 가량 높았다. 20년 운영 시 탄소배출량은 GSHP 시스템 72,648 kgCO2-eq, ASHP 시스템 118,181 kgCO2-eq으로 ASHP 시스템이 39% 높았다. (3) GSHP 시스템은 높은 COP 확보로 운전단계에서 탄소배출량을 ASHP 시스템에 비해 연간 42% 저감할 수 있고, GSHP 시스템의 시공 단계에서 발생하는 탄소배출량은 2년 이내에 상쇄시킬 수 있다. 향후, 더욱 다양한 신재생에너지 열원을 고려하여 전 과정평가 실시를 통해 복합 시스템의 우위성 및 이산화탄소 배출량 저감 효과에 대한 신뢰성을 높일 예정이다. 또한, 이산화탄소 배출량뿐만 아니라 7대 환경영향범주를 모두 고려하여 환경영향평가를 실시할 계획이다. In this study, the performance of two renewable energy systems, ground source heat pump (GSHP) system and air source heat pump (ASHP) system, was analyzed through dynamic energy simulation, and carbon emissions were quantitatively calculated through a life cycle assessment method based on the simulation results. The carbon emissions of the energy systems were calculated by dividing the life cycle evaluation stage into four categories: production, construction, operation, and disposal, and the calculation of carbon emissions in the operation stage was based on the annual performance analysis of the dynamic energy simulation. For 1 year of operation, the GSHP system had 14% higher carbon emissions than the ASHP system, while for 20 years of operation, the ASHP system had 39% higher carbon emissions than the GSHP. Compared to the ASHP system, the GSHP system can reduce carbon emissions in the operating stage by 42% per year by securing higher COP, and within 2 years, the carbon amount in the entire process can be lower than in the ASHP system. KCI Citation Count: 0